BODY, GIMNASTICS AND SEXUALITY IN THE HYGIENIC AND EUGENIC REFERENCE MANUALS IN CHILE 1870-1938 - Durán Sandoval, Manuel (Revista de Historia Social y de las Mentalidades, 2015)
This article tackles the conformation of a  positive eugenic speech heir to the ambientalist/ environmentalist and racial hygienic theories of  the late 19th century. This tendency strengthened  between 1925 and 1938 through the conformation  of an institutional structure and social programmes  with strong positive eugenic shades, considering  the body and the “character” of youth as the  amalgam of the nation. In this context, from the  late 19th century, attempts were developed to  build a public medicine that would promote an  education and youth preservation programme. This  ambientalist/environmentalist initiatives pretended  to enhance the young physical and moral skills  through diets, hygiene and gymnastics.
Keywords: Hygienism; Eugenics; Sexuality; Gymnastics; Gender; Education; Medical area